Pengaruh Lokasi, Kualitas Pelayanan, dan Variasi Produk terhadap Loyalitas Konsumen di Kaki Empat Petcare Kediri - Clarissa Viola Arshy; Taufik Akbar; Zulfia Rahmawati (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to determine the effect of the independent variables Location, Service Quality, and Product Variety—on the dependent variable, namely Customer Loyalty, at Kakiempat Petcare Kaliombo, Kediri City. This research applies a quantitative method, utilizing multiple linear regression analysis with the aid of SPSS 26 software. The sampling technique employed was incidental sampling. Based on the results, it can be concluded that Location has a partial and positive influence on Customer Loyalty. Service Quality has a partial and positive influence on Customer Loyalty. Product Variety also has a partial and positive influence on Customer Loyalty. Furthermore, Location, Service Quality, and Product Variety simultaneously have a positive and significant effect on Customer Loyalty. It is expected that through this research, Kakiempat Petcare Kaliombo, Kediri City, can maintain its strategic and easily accessible location, continuously uphold high service quality, and regularly update product variations in line with market trends, so that customers feel they have many choices and are encouraged to make repeat purchases.